2013
DOI: 10.1186/bcr3457
|View full text |Cite|
|
Sign up to set email alerts
|

Novel sorafenib analogues induce apoptosis through SHP-1 dependent STAT3 inactivation in human breast cancer cells

Abstract: IntroductionSignal transducers and activators of transcription 3 (STAT3) signaling is constitutively activated in various cancers including breast cancer and has emerged as a novel potential anti-cancer target. STAT3 has been demonstrated to be a target of sorafenib, and a protein tyrosine phosphatase Src homology 2-domain containing tyrosine phosphatase 1 (SHP-1) has been demonstrated to downregulate p-STAT3 via its phosphatase activity. Here, we tested the efficacy of two sorafenib analogues, SC-1 and SC-43,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…We also provided the first evidence demonstrating that regorafenib is a novel enhancer of SHP-1 tyrosine phosphatase activity, which dramatically decreases p-STAT3 Tyr705 expression. Ample evidence suggests that SHP-1 functions as a tumor suppressor that directly targets the oncogenic expression of p-STAT3 Tyr705 that is crucial for the tumor survival and cellular proliferation [6, 21-24]. Our study demonstrated for the first time that regorafenib activated an SHP-1 tumor suppression pathway by directly enhancing SHP-1 activity, and induced apoptosis and tumor suppression in CRC.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We also provided the first evidence demonstrating that regorafenib is a novel enhancer of SHP-1 tyrosine phosphatase activity, which dramatically decreases p-STAT3 Tyr705 expression. Ample evidence suggests that SHP-1 functions as a tumor suppressor that directly targets the oncogenic expression of p-STAT3 Tyr705 that is crucial for the tumor survival and cellular proliferation [6, 21-24]. Our study demonstrated for the first time that regorafenib activated an SHP-1 tumor suppression pathway by directly enhancing SHP-1 activity, and induced apoptosis and tumor suppression in CRC.…”
Section: Discussionmentioning
confidence: 56%
“…Importantly, our previous studies have clearly demonstrated that SHP-1 is a negative regulator of p-STAT3 Tyr705 [6, 21-24] that is highly expressed in cancer cells and is crucial for growth, survival, and metastasis of cancer cells during cancer progression. Therefore, we clarify whether the sorafenib analog regorafenib (Fluoro-sorafenib) acts as a direct enhancer of SHP-1 by which enhanced SHP-1 activity directly downregulates p-STAT3 Tyr705 and eventually contributes to apoptosis in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Sorafenib has been shown to activate various PTPs in different cell types [14,30-32]. Herein, the effect of sorafenib on SHP-1 and/or PTEN activation was evaluated in BC cells via western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sorafenib is used for HCC treatment, although it is effective for only a short time. SC-1 inhibits Stat3 phosphorylation and induces apoptosis in a breast cancer cell line (31). We treated cells with sorafenib (multikinase inhibitor, including c-Kit) and/or stattic (Stat3 inhibitor).…”
Section: Resultsmentioning
confidence: 99%